Study of Nutritional and Organoleptic Quality of Formulated Juices from Jujube (Ziziphus lotus L.) and Dates (Phoenix dactylifera L.) Fruits. (31st March 2020) - Benidir, Meryem; El Massoudi, Soukaina; El Ghadraoui, Lahsen; Lazraq, Abderrahim; Benjelloun, Meryem; Errachidi, Faouzi
Abstract : The present work aims to elaborate many juice formulas (F1 to F8) from two dried fruits (jujubes: Ziziphus lotus L. and dates: Phoenix dactylifera L.). Physicochemical and biochemical characterization of the formula juices shows that juices rich in dates fruits (F1, F3, F5, and F7) are loaded, on average, in total sugars (129.5 g/l), proteins (3.02 g/l), lipids (1.08 g/l), and carotenoid (0.02 mg/l), while juices rich in jujube fruits (F2, F4, F6, and F8) are overloaded, on average, in phenolic compounds (697 mg/l), flavonoids (6.32 mg/l), condensed tannins (2.1 mg/l), hydrolysable tannins (359.5 mg/l), and viscosity (1.062 mm 10–3 s). All formulations developed have a pH that rotates between 5.12 and 5.20. Total antioxidant capacity (CAT) reveals that formulations F1, F3, F5, and F7 show a strong activity compared to the other formulas. The DPPH test shows that all formulated juices have the same antioxidant profile with IC50 values lower than the template (BHT and Vit C). The FRAP test reveals that F2, F4, F6, and F8 formulas have a strong reducing power. Organoleptic evaluation by a jury shows that F4 formula is the best in terms of odor, aroma, and aftertaste agreeability.